Smartphone Use and Academic Performance: A Literature Review - Simon Amez; Stijn Baert (Institute of Labor Economics (IZA), 2019)
We present the first systematic review of the scientific literature on smartphone use and academic success. We synthesise the theoretical mechanisms, empirical approaches, and empirical findings described in the multidisciplinary literature to date. Our analysis of the literature reveals a predominance of empirical results supporting a negative association between students' frequency of smartphone use and their academic success. However, the strength of this association is heterogeneous by (a) the method of data gathering, (b) the measures of academic performance used in the analysis, and (c) the measures of smartphone use adopted. The main limitation identified in the literature is that the reported associations cannot be given a causal interpretation. Based on the reviewed findings and limitations, directions for further research are discussed.
Keywords: I21; I23; L86; 330; smartphone use; smartphone addiction; academic performance; literature review; causality